If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -45 = 56 Reorder the terms: -45 + 3x = 56 Solving -45 + 3x = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + 3x = 56 + 45 Combine like terms: -45 + 45 = 0 0 + 3x = 56 + 45 3x = 56 + 45 Combine like terms: 56 + 45 = 101 3x = 101 Divide each side by '3'. x = 33.66666667 Simplifying x = 33.66666667
| 8+5x=7x+8 | | -3(-4p+5)=5(6p+15) | | -14.3=5.7-4y | | 4a-b=.5 | | 3x+13-6x=15x+12x-5 | | x-(4.50+1.99+0.39)=13.12 | | 3x+2y-2=180 | | 3y=2x-15 | | y=x^2-8x+195 | | (2x^2+6x-3)+(2x^3-3x+2)= | | 3x+2=-3x+20 | | 2x+8=3x*x+4 | | -9-x=6x-79 | | -5x+11x-49=77 | | 2x+3+y+2=180 | | (r-3s+t)(2r-s+t)=0 | | 6y=4-1.69 | | 24=3(n+15) | | 3x+2=-3+20 | | 2(4y-5x)=6y-20 | | 9=4c-11 | | 18372747267284717839274728726472+98377778777777293771898472984727384774918999999999999999917373892946584456673485753756427426427538673=1 | | 2[4+2(5-x)-2x]=4(7+2x) | | -7x-2+x=-62 | | =(2x^3-7x^2+7x)+(2x^3+9x^2-14x) | | 5(2n+5)=6(8n+6)+5 | | 8x-3-3x=5x | | 35=8x-53 | | 2x+22=4x+4 | | (3x+5)+(2x-7)+x=180 | | 123456789+123456789=1 | | -7(n+4)+29=-4n-5 |